Synthesis of new derivatives of aryl-clonazepam via Suzuki Cross-coupling reaction - Salman, Mohammed Abed Al-Hussein; Abdul-Rida, Nabeel Abed (European Journal of Chemistry, 2016)
A new series of aryl clonazepam derivatives (11-16) have been synthesized by employing Suzuki Cross-coupling reaction, which includes the reaction of clonazepam with suitable derivative boronic acid at the presence of Pd(PPh3)4 as catalyst, and Na2CO3 as a base. The structures of the newly synthesized compounds were assigned by 1H, 13C and 2D NMR spectroscopic techniques.